ECOLITERACY IN UTILIZING PLASTIC WASTE TO ECOBRICK THROUGH PROJECT BASED LEARNING ON SOCIAL STUDIES LEARNING - Rahmawati, Annisa (International Journal Pedagogy of Social Studies, 2019)
ABSTRACTThis research is motivated by researchers concern for the environment, class VIII A SMP Negeri 45 Bandung is a problem in this study. Researchers take action by observing to increase awareness of the environment In social studies learning is required to interact directly with social studies learning resources as well as understanding ecoliteracy, a teacher can develop through the assignment of ecobricks in utilizing plastic waste. The task can be a solution to solve environmental problems with knowledge. Through ecobrick, it is more active to find answers to environmental problems using attractive and effective learning models. The method used in this research is classroom action research (CAR). The method used is the classroom action research (CAR) method using the Lewin design according to Elliot which is carried out in each cycle, namely the problem identification stage, field checking, action planning, observation and reflection. The data source of this research is the result of the ecobrick assignment. This research was conducted through three cycles: the first cycle the percentage obtained was included in the less category. Then in the second cycle an increase so that the percentage obtained falls into the sufficient category. Then in the third cycle experienced a significant increase included in both categories. Therefore, this model-based learning model is appropriate for students to use.Â Keywords: Ecobrick, Ecoliteracy, Project Based Learning